Development of Elementary School Mathematics Textbooks Based on Augmented Reality to Support the Profile of Critical and Creative Pancasila Students - Joko Sulianto; Achmad Buchori; Noviana Dini Rahmawati (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
The implementation of three-dimensional textbooks in both public and private elementary schools within the Semarang city area remains limited with most institutions still relying on conventional printed versions. However, AR-based mathematics textbooks—already adopted in parts of Indonesia—offer interactive visual experiences that can enhance students’ critical and creative thinking. This study employed a Research and Development (R&D) approach using the Multimedia Development Life Cycle (MDLC) model developed by Luther-Sutopo, which includes six phases: concept development, design, material collection, assembly, testing, and distribution. A limited trial was conducted at SDN Sawah Besar 01 Semarang. The outcomes of the study are as follows: (1) The development of the 2nd grade thematic AR textbook linked to the Pancasila Student Profile, featuring engaging and interactive AR content; (2) high validation scores from experts—89 (material) and 87.75 (media)—indicating strong suitability for use in thematic learning at the second-grade level; (3) Multivariate Analysis of Variance (MANOVA) results demonstrated a statistically significant improvement (p < 0.05) in critical and creative thinking among students using the AR textbook compared to the control group. These results suggest that AR-enhanced thematic textbooks are both effective and viable for wider adoption in elementary schools across Semarang.